The Effect of Online Reviews and Risk Perception on Trust and Its Impact on Consumer Purchase Decisions on Marketplaces (Shopee, Tokopedia, Lazada, and Blibli) - Rifaldi Rifaldi; Henny Welsa; Putri Dwi Cahyani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The development of the marketplace in Indonesia has change behavior consumer in the process of taking decision purchases. Online reviews are one of the source information main used​ consumer For evaluate quality product, credibility sellers, and platform security before do transactions. Research This aim For analyze the influence of online reviews and perceptions risk to decision purchase consumer with trust as variables mediation in the marketplaces Shopee, Tokopedia, Lazada, and Blibli. Research use approach quantitative with type of explanatory research. Data collection techniques sample using purposive sampling with amount respondents as many as 140 marketplace users in Indonesia who have read or write review product. Data analysis was performed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The research results show that online reviews are influential positive and significant to trust consumers and decisions purchase. Perception risk also has an effect significant to trust and decisions purchases, where the more low perceived risk​ consumer so the more tall level beliefs and tendencies do purchase. Apart from that, trust proven influential positive and significant to decision purchase as well as capable mediate connection between online reviews and perception risk to decision purchase. Findings This confirm that trust become factor key in push decision purchase consumers in the marketplace. Research This give implications practical for marketplace managers for increase quality system reviews, security transactions, as well as protection consumers to build trust and increase decision purchase consumers.